Social Support Mediates the Effect of Burnout on Health in Health Care Professionals - Ruisoto, Pablo; Ramírez, Marina R.; García, Pedro A.; Paladines-Costa, Belén; Vaca, Silvia L.; Clemente-Suárez, Vicente J. (Frontiers in Psychology, 2021)
Burnout is characterized by emotional exhaustion and caused by exposure to excessive and prolonged stress related to job conditions. Moreover, burnout is highly prevalent among health care professionals. The aim of this study is, first, to examine the mediating role of social support over the effect of burnout in health care professionals and, second, to explore potential gender differences. A convenience sample of 1,035 health professionals from Ecuador, including 608 physicians and 427 nurses (68% women, with and age M = 40 + 9 years old), was surveyed using the Maslach Burnout Inventory (MBI), Social Support Survey (MOS), and General Health Questionnaire (GHQ-28) as measures of burnout, social support, and general health, respectively. Social support was found to mediate the negative effects of burnout on health regardless of gender. Differences across the three dimensions of burnout and health are further discussed, along with their implications for designing effective burnout interventions for health care professionals in Ecuador.